The Protestant Ethic as an ideological justification of capitalism - Buchholz, Rogene A. (Journal of business ethics, 1983)
The Protestant Ethic not only had behavioral implications, as Max Weber and others have pointed out, it also had ideological implications in providing a moral legitimacy for capitalism. The Protestant Ethic provided a moral justification for the pursuit of profit and the distribution of income that are a part of the system. Currently there is a good deal of intellectual concern about the moral legitimacy of the capitalist system. Thus it is important to trace the origins of the Protestant Ethic and recover the ideological functions it performs in a capitalistic society.